THE EFFECTS OF REALITY PEDAGOGY ON THE ACADEMIC PERFORMANCE AND MOTIVATION TO LEARN OF GRADE 7 PHYSICS STUDENTS - Iris April L Ramirez (State Islamic University of North Sumatra Indonesia, 2018)
The study investigated the effects of Reality Pedagogy on the academic performance and motivation to learn of Grade 7 Physics students. It was conducted at Bukidnon State University – Secondary School Laboratory for the school year 2015-2016. A quasi-experimental design was utilized in the study. Developed lessons about Motion in One Dimension, Waves and Sound as well as a 30-item paper and pencil performance test were assessed and evaluated by panel of experts with their respective specialized field. A Physics Motivation Questionnaire adopted from Glynn was modified and also used. The data gathered used statistical technique such as mean and standard deviation. Also, the one-way analysis of covariance (ANCOVA) and t-test both at 0.05 level of significance were employed. Finding revealed that the posttest of the experimental group shows very satisfactory result compared with the control group which was only satisfactory. Further, there was no significant difference in the academic performance between the Grade 7 students taught by Reality Pedagogy and of the students not using Reality Pedagogy. However, there is an improvement in the academic performance of the two groups regardless with or without the intervention. The study showed that both the control and the experimental groups were moderately motivated to learn physics.